Playing with languages: code-switching between Italian-Brazilian immigrants during a ruzzola tournament - Ferroni, Roberta (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2017)
This article examines the language strategies, in particular code-switching, implemented by a group of Italian immigrants who live in the city of São Paulo and are enrolled in a ruzzola tournament. In this bilingual context we saw that, in accordance with the language skills of the players and interaction management requirements, the language of interaction is constantly negotiated. The data analyzed tend to indicate that even very minimal and rudimentary use of the language can help contribute to the individual’s Italian identity, and that certain activities that are perceived as traditional in the culture of origin can function as a vehicle for renewed interest in the language of the country of origin. This study adopts as our theoretical and methodological reference the bilingual conversation procedural model developed by Auer (1984), Alfonzetti (1992), De Fina (2007a, 2007b), and the contextualization theory of Gumperz (1982).